2019
DOI: 10.1111/faf.12349
|View full text |Cite
|
Sign up to set email alerts
|

Turbine entrainment and passage of potadromous fish through hydropower dams: Developing conceptual frameworks and metrics for moving beyond turbine passage mortality

Abstract: Potadromous fishes are vulnerable to involuntary entrainment through hydropower turbines. However, turbines can also provide a downstream passage route for potadromous fish. Here, we review evidence for turbine entrainment and passage in potadromous fish, and evaluate the effects of these processes on upstream and downstream populations. We develop conceptual frameworks and metrics to quantify vulnerability to turbine entrainment removals, and to quantify the efficiency of turbines as a downstream passage rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 93 publications
(184 reference statements)
3
44
0
Order By: Relevance
“…Trash racks are placed in front of pumping and hydropower stations to prevent large debris getting into the turbines and are the first physical obstacles fish encounter while approaching these structures. Most studies on the effects of pumping or hydropower stations with trash racks focus on the risk of entrainment, but more focus should be directed to behavioural responses of fish in the vicinity of these structures in relation to entrainment risk (Harrison et al, 2019). An eel approaching these structures perceives multiple cues that might trigger a change in its behaviour, for example, at larger distances underwater sound emitted by the stations (Behrmann‐Godel & Eckmann, 2003) and near the trash rack and pumping stations water flows change in direction and increase in speed (Piper et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Trash racks are placed in front of pumping and hydropower stations to prevent large debris getting into the turbines and are the first physical obstacles fish encounter while approaching these structures. Most studies on the effects of pumping or hydropower stations with trash racks focus on the risk of entrainment, but more focus should be directed to behavioural responses of fish in the vicinity of these structures in relation to entrainment risk (Harrison et al, 2019). An eel approaching these structures perceives multiple cues that might trigger a change in its behaviour, for example, at larger distances underwater sound emitted by the stations (Behrmann‐Godel & Eckmann, 2003) and near the trash rack and pumping stations water flows change in direction and increase in speed (Piper et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…turbine entrainment mortality is frequently <100%, and often~30% (Pracheil, DeRolph, Schramm, & Bevelhimer, 2016;Wilkes, Webb, Baumgartner, et al, 2018), entrainment survivors can disperse into downstream environments and can augment downstream populations (Harrison et al, 2019). While the vulnerability of anadromous salmonid populations to turbine entrainment has been well studied (e.g., Calles & Greenberg, 2009;Silva et al, 2017), less is known about the turbine entrainment vulnerability of potadromous fish populations (Rytwinski et al, 2017).…”
mentioning
confidence: 99%
“…When the number of entrained individuals is high, seasonal patterns of entrainment vulnerability can be quantified directly (Smith & Brown, 2002). However, when the number of observable entrainment events are restricted due to sample size, seasonal patterns of forebay (the area of a reservoir in the vicinity of the dam) occupancy, can be used as proxy for entrainment vulnerability (Harrison et al, 2019;Martins et al, 2013). Furthermore, given that fish that are located close to the dam forebay are likely at higher risk of entrainment than fish that are located a long distance away, fish proximity to the forebay, can also be used a measure of entrainment vulnerability, and to help understand seasonal patterns of entrainment vulnerability (Harrison et al, 2019).…”
mentioning
confidence: 99%
“…In this case the physical traits of the fish community present at the study site is representative of a range of fishes found across North America and differ from the species tested in Europe. If specific species are at a greater risk of mortality or certain injury types, steps can be taken to mitigate risk to the fish community (Algera et al, 2019). In my investigation into this matter I was able to identify sublethal and lethal injury rates and compare these measures across the treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies of VLH technology have focused on the consequences of entrainment rather that the likelihood of entrainment. Entrainment risk for resident fish populations is an important metric in understanding the potential ecological consequences of hydropower development (Harrison et al, 2019). Given the lack of research on this topic in small to middle sized rivers with low head dams, this research addresses an important gap in VLH turbine risk assessment and more broadly in fish-hydropower interactions.…”
Section: Introductionmentioning
confidence: 99%